Frances Power Cobbe (1822-1904) et la naissance du mouvement contre l’expérimentation animale - Émilie Dardenne (Cahiers Victoriens et Edouardiens)
In reaction to the growing power of doctors and scientists, the second half of the Victorian era saw the emergence of an organized movement against animal experimentation. Led by the journalist Frances Power Cobbe, the movement was opposed to the definition of morals dictated by science which, surrounded by a rising materialism, made human health the new priority and thus made animals mere instruments of research. Armed with ethical arguments, antivivisectionists gave care and empathy a new dimension. They intended to spread compassion beyond the sphere of mankind. How can we account for the birth of this movement ? What did it imply ? How did the tension between the « scientifically correct » and the « ethically acceptable » evolve ? I will try to shed light on these questions by looking more precisely at the arguments of the head of the movement : Frances Power Cobbe.